Case Report: Genomic insights and personalized treatment in dual primary esophageal squamous cell carcinoma and gastric adenocarcinoma - Miao, Chuanwang; Guo, Yaning; Yang, Huili; Zhu, Shan; Chen, Yuanji; Zhao, Wei; Hu, Xudong (Frontiers in Oncology, 2025)
Dual primary malignancies in the upper gastrointestinal tract are rare and pose diagnostic and therapeutic challenges. This study reports a case of synchronous esophageal squamous cell carcinoma (ESCC) and gastric adenocarcinoma (GAC), highlighting the role of genetic profiling in personalized treatment. A 78-year-old female patient was diagnosed with stage IIB ESCC and stage IIIA GAC. Due to surgical ineligibility, she received chemoradiotherapy and immunotherapy. Next-generation sequencing (NGS) was performed to identify potential genetic drivers. Genetic analysis revealed common chromosomal amplifications on 19p and 21q but no shared driver mutations, suggesting independent tumor origins. ESCC exhibited amplifications of MCL1, RECQL4, NKX2-1, PARP10, RSPO1, MUCL, and WTIP, while GAC showed deletions of APC and PRKG1, along with amplifications of ARRDC1 and NRARP. The patient achieved stable disease without recurrence following chemoradiotherapy and Sintilimab immunotherapy. This case underscores the role of genetic alterations in dual primary cancers and demonstrates the feasibility of precision treatment.